2021
DOI: 10.1186/s12301-021-00173-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of illness perception and financial toxicity on the quality of life of prostate cancer patients

Abstract: Background Cancer of the prostate (CaP) is a public health problem that affects the male genitourinary system causing a significant threat to men’s quality of life (QoL). Experiencing financial constraints and poor illness perception may further compromise the QoL of men with CaP. Methods Aim: To examine the relationship between financial toxicity and illness perception with quality of life in men with CaP. The descriptive cross-sectional study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…Interestingly, our included studies showed that the correlation strengths between financial toxicity and overall HRQOL were slightly stronger in studies that used English instruments (median = 0.53, range = 0.33-0.73) 57,58,60,62,64,66,73,81 than those in other languages, for example, Mandarin Chinese, Italian, and Arabic (median = 0.43, range = 0.34-0.52), 51,55,67,72,79,80 and conducted in countries with universal health coverage (median = 0.49, range = 0.34-0.73) 55,58,66,72,79,80 than those without (median = 0.42, range = 0.33-0.63). 51,57,60,62,64,67,73,81 Nevertheless, we had inadequate number of studies to further examine (eg, performing subgroup analysis) the potential impact of instrument language or universal health coverage on the association between financial toxicity and HRQOL. 46 Exploring the role of universal health coverage and mitigation strategies in alleviating financial toxicity and improving HRQOL may be an important future research direction.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Interestingly, our included studies showed that the correlation strengths between financial toxicity and overall HRQOL were slightly stronger in studies that used English instruments (median = 0.53, range = 0.33-0.73) 57,58,60,62,64,66,73,81 than those in other languages, for example, Mandarin Chinese, Italian, and Arabic (median = 0.43, range = 0.34-0.52), 51,55,67,72,79,80 and conducted in countries with universal health coverage (median = 0.49, range = 0.34-0.73) 55,58,66,72,79,80 than those without (median = 0.42, range = 0.33-0.63). 51,57,60,62,64,67,73,81 Nevertheless, we had inadequate number of studies to further examine (eg, performing subgroup analysis) the potential impact of instrument language or universal health coverage on the association between financial toxicity and HRQOL. 46 Exploring the role of universal health coverage and mitigation strategies in alleviating financial toxicity and improving HRQOL may be an important future research direction.…”
Section: Discussionmentioning
confidence: 83%
“…Akin-Odanye et al (2021) 51 Higher financial toxicity is associated with worse HRQOL -COST and FACT-P correlation: r = 0.416 (P , .010) -COST and FACT-P regression: B = 0.392, b = 0.181 (P , .…”
Section: Author (Year) Main Finding Statistical Analysismentioning
confidence: 98%
See 3 more Smart Citations